Existence of Values of Pakkio Bunting in Micro-Structure in A Review of Van Dijk’scritical Discourse Analysis - Muhammad Ali; Fien Pongpalilu; Ince Nasrullah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The type of research is descriptive-qualitative that describing how existence of values of Pakkio Bunting in oral literature of Makassar.The instrument of research is researcher as key instrument. Researchers try to interpret carefully through experience as native speakers. Data analysis technique is conducted through 3 (three) cycles namely data collection, data reduction, and drawing conclusions and verification. Van Dijk’s theory as an analytical tool with grand theory of hermeneutics as an analytical tool or interpreter.Based on the results of the analysis found several values, this relates to the values of (1) happiness, (2) togetherness, (3) feelings, (4) ideals and expectations, (5) prayer, (6) degree of parents, (7) respect, (8) responsibility, (9) obedience to parents, (10) humility, (11) loyalty, (12) advice, and (13) politeness. All values in the poem describe the existence of Makassar people in local and universal life.The research provides invaluable benefits for Indonesian and Regional Language and Literature teachers in developing learning materials in class, especially in learning appreciation of poetry and prose of local culture in each region or country.